التفكیر الابداعي من منظور إسلامي، وتطبيقاته لدى عضو هيئة التدريس الجامعي (طرائق التدريس أنموذجاً) - عبدالله, ناصح كريم (Sulaimani Journal for Humanities, 2021)
The current study aims to highlight creative thinking, its importance and skills in teaching, and to work to stimulate thinking among students and students in the academic community, through a scientific methodology based on the self-development of a university faculty member, and the development of thinking skills in the academic community. This is in order to establish a creative developed environment that serves the community and contributes to its development and advancement. The researcher has used the descriptive method, as it is more appropriate for the research conducted in the humanities. The paper has come out with a number of results and made a number of recommendations, which the researcher referred to at the end of the research and that can serve the educational process.
Keywords: التفكیر الابداعي عضو هيئة التدريس الجامعي طرائق التدريس